Emotional intelligence training among the healthcare workforce: a systematic review and meta-analysis - Powell, Chris; Brown, Taylor; Yap, Yang; Hallam, Karen; Takac, Marcel; Quinlivan, Tara; Xenos, Sophia; Karimi, Leila (Frontiers in Psychology, 2024)
The healthcare sector is acknowledged as a complex and challenging field.Increasingly, research highlights the importance of healthcare workers' internal social and emotional skills in managing their well-being and enhancing their capacity to provide patient care and support to colleagues. Emotional Intelligence (EI) has been identified as a key factor in improving the health and performance of healthcare workers, leading to the implementation of numerous programs aimed at enhancing EI. Objective: This meta-analysis aims to evaluate the effectiveness of EI training interventions among healthcare workers, focusing on various intervention designs and their impact on EI improvement. Methods: The review encompassed 17 longitudinal studies, each implementing EI training interventions for healthcare workers aged 18 and over. The studies employed a variety of research designs. Results: All studies demonstrated an increase in EI following the intervention. However, methodological limitations within these studies might have led to an overestimation of the actual effects of the interventions. Conclusion: While the reviewed studies indicate a positive trend in EI enhancement postintervention, the potential overestimation of effects due to methodological flaws necessitates caution. The findings underline the need for future research to explore the optimal duration and delivery methods for EI training in healthcare settings.